Integrated inertial-impedance cytometry for rapid label-free leukocyte isolation and profiling of neutrophil extracellular traps (NETs). Issue 10 (25th April 2019) - Petchakup, Chayakorn; Tay, Hui Min; Li, King Ho Holden; Hou, Han Wei
Abstract : A novel integrated inertial-impedance cytometer for rapid and label-free electrical profiling of neutrophil extracellular trap formation (NETosis). Abstract : Circulating leukocytes are indispensable components of the immune system, and rapid analysis of their native state or functionalities can help to unravel their pathophysiological roles and identify novel prognostic biomarkers in health and diseases. Herein we report a novel high throughput "sample-in-answer-out" integrated platform for continuous leukocyte sorting and single-cell electrical profiling in a label-free manner. The multi-staged platform enables isolation of neutrophils and monocytes from diluted or lysed blood samples directly within minutes based on Dean flow fractionation (DFF) (stage 1). Next DFF-purified leukocytes are inertially focused in serpentine channels into a single stream (stage 2) prior to impedance detection (stage 3). As a proof-of-concept for neutrophil functional characterization towards diabetes testing, we characterized the formation of neutrophil extracellular traps (NETosis) of healthy and glucose-treated neutrophils and observed significant changes in dielectric properties (size and opacity) between both groups. Interestingly, the NETosis profiles induced by calcium ionophore (CaI) and phorbol 12-myristate 13-acetate (PMA) were also electrically different, which could be attributed to the differential rates of cell enlargement and attenuated membrane permeability. Taken together, these results clearly demonstrated the potential of the developed platform for rapid (∼mins) and label-free leukocyte profiling and the use of impedance signatures as novel functional biomarkers for point-of-care testing in diabetes.